(untitled) (Fiep Bulletin - online, 2014)
The muscle dysmorphia, also known as Adonis complex or reverse anorexia is a psychological syndrome or frame marked body dissatisfaction and malaise, in which the individual feels weak and poorly muscled, causing an excessive practice of physical exercises and dependency . Considering the implications of the disorder for the physical and mental health of individuals, this article aimed to characterize the muscle dysmorphia, from the discussion of its social aspects, covering the topics: definition, clinical characteristics, diagnostic criteria, risk groups, factors that trigger disorders, cultural and social implications for individuals.